Algorithms and Data Structures 14th International Symposium, WADS 2015, Victoria, BC, Canada, August 5-7, 2015. Proceedings - Dehne, Frank.; Dehne, Frank.; Sack, Jörg-Rüdiger.; Sack, Jörg-Rüdiger.; Stege, Ulrike.; Stege, Ulrike. (Theoretical Computer Science and General Issues ;, 2015)
This book constitutes the refereed proceedings of the 14th Algorithms and Data Structures Symposium, WADS 2015, held in Victoria, BC, Canada, August 2015. The 54 revised full papers presented in this volume were carefully reviewed and selected from 148 submissions. The Algorithms and Data Structures Symposium - WADS (formerly Workshop on Algorithms And Data Structures), which alternates with the Scandinavian Workshop on Algorithm Theory, is intended as a forum for researchers in the area of design and analysis of algorithms and data structures. WADS includes papers presenting original research on algorithms and data structures in all areas, including bioinformatics, combinatorics, computational geometry, databases, graphics, and parallel and distributed computing.